2018
DOI: 10.1097/cej.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in TLR1, TLR2, TLR4, and TLR10 of Helicobacter pylori-associated gastritis: a prospective cross-sectional study in Thailand

Abstract: The toll-like receptors (TLRs) mediate the recognition of Helicobacter pylori and initiate the innate immune response to infection. We hypothesized those genetic polymorphisms in the TLR1, TLR2, TLR4, and TLR10 influence bacterial infection, affecting susceptibility H. pylori to disease outcomes. Genomic DNA was extracted and genotypes of TLR1 (rs4833095), TLR2 (rs3804099 and rs3804100), TLR4 (rs10759932), and TLR10 (rs10004195) polymorphism were detected by the TagMan single-nucleotide epolymorphisms genotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Association between TRL1 rs4833095 and tuberculosis susceptibility [36, 37], increased risk of IgA nephropathy [38], Crohn's disease and ulcerative colitis [39], susceptibility for alopecia areata [40], increased mortality in patients with sepsis following traumatic injury [35] have been found in various studies. The discovery of association between TLR1 SNP rs4833095 and H. pylori seroprevalence in a GWAS in European descent population [20] was replicated in the Thai population: the TLR1 rs4833095, C allele was associated with a significantly increased risk for H. pylori infection [19]. Moreover, the above mentioned SNP along with TLR10 rs10004195 was associated with GC in H. pylori infected subjects in a Malaysian population [18].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Association between TRL1 rs4833095 and tuberculosis susceptibility [36, 37], increased risk of IgA nephropathy [38], Crohn's disease and ulcerative colitis [39], susceptibility for alopecia areata [40], increased mortality in patients with sepsis following traumatic injury [35] have been found in various studies. The discovery of association between TLR1 SNP rs4833095 and H. pylori seroprevalence in a GWAS in European descent population [20] was replicated in the Thai population: the TLR1 rs4833095, C allele was associated with a significantly increased risk for H. pylori infection [19]. Moreover, the above mentioned SNP along with TLR10 rs10004195 was associated with GC in H. pylori infected subjects in a Malaysian population [18].…”
Section: Discussionmentioning
confidence: 86%
“…The PRRs recognize bacterial lipopolysaccharides (LPS) and induce the secretion of pro-inflammatory molecules [18]. Polymorphisms of TLR genes can confer host susceptibility to H. pylori infection as well as to H. pylori related diseases by modulating the release of pro-inflammatory cytokines, which underline gastric inflammation and the immune response to H. pylori [19]. A recent genome-wide association study (GWAS) revealed significant association of single-nucleotide polymorphisms (SNPs) in the TRL1 gene with susceptibility of H. pylori in an European descent population [20].…”
Section: Introductionmentioning
confidence: 99%
“… 18 TLR10 (rs10004195) is linked with infection susceptibility, where the frequency of the TT genotype is reported to be 66% in H pylori- positive cases from a Chinese population. 29 Therefore, the T allele of TLR10 rs10004195 polymorphism showed an increased risk of chronic atrophic gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the TLR1 rs4833095 CC homozygous wild type and the TLR10 rs10004195 AA homozygous wild type were associated with H. pylori susceptibility and increased risk of H. pylori infection in chronic gastritis patients (25). Moreover, TLR10 polymorphism was associated with H. pyloriinduced inflammation with gastric mucosal patterns, suggesting that the AA homozygous wild type contributes to severe inflammation in H. pylori-associated gastritis (26).…”
Section: Discussionmentioning
confidence: 99%